2009
DOI: 10.3233/jad-2009-1163
|View full text |Cite
|
Sign up to set email alerts
|

Impact of APOE on the Healthy Aging Brain: A Voxel-Based MRI and DTI Study

Abstract: Neuroimaging studies of apolipoprotein E (APOEε4) have implicated its association with brain atrophy in Alzheimer's disease. To date, few studies have used automated morphological analysis techniques to assess APOEε4-related brain structure change in both gray and white matter in nondemented older adults. Nondemented (CDR = 0, n = 53) subjects over 60 had MRI, diffusion tensor imaging, and neurocognitive assessments. We assessed differences in cognition and brain structure associated with APOEε4 genetic variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
182
4
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(207 citation statements)
references
References 84 publications
(85 reference statements)
15
182
4
1
Order By: Relevance
“…Although FA was not altered, widespread significant increases in MD were observed in APOE ε4-carriers. This is in accordance with several other studies that reported effects of the APOE ε4 allele on WM integrity in brain tracts such as parahippocampal WM 38,53 and the corpus callosum 39,54 whereas a recent study did not replicate these results 55 .…”
Section: Effect Of Apoe Genotype On Wmsupporting
confidence: 69%
See 1 more Smart Citation
“…Although FA was not altered, widespread significant increases in MD were observed in APOE ε4-carriers. This is in accordance with several other studies that reported effects of the APOE ε4 allele on WM integrity in brain tracts such as parahippocampal WM 38,53 and the corpus callosum 39,54 whereas a recent study did not replicate these results 55 .…”
Section: Effect Of Apoe Genotype On Wmsupporting
confidence: 69%
“…59,60 Although APOE genotype effects were observed within WM regions in both the younger and the older group, we found that GM structure did not differ between APOE ε4-carriers and non-carriers. This was interesting because we expected that at least in the older group the higher risk of AD for APOE ε4-carriers would show in GM changes, especially in regions affected early by AD 61 , as was shown in two studies 20,53 . However, other studies also failed to observe APOE-related structural GM differences in healthy subjects.…”
Section: Effect Of Apoe Genotype On Wmmentioning
confidence: 95%
“…[34][35][36][37][38][39][40][41] The present study recruited individuals without subjective or objective cognitive impairment, hence subjects with normal cognition, to test the effects of APOE4 on the brain functioning of WM by using BOLD fMRI. Performance of n-back WM was not different between groups (P ϭ .41-.85), similar to the findings of a previous publication.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging work in patients has demonstrated reduced activation of the hippocampal formation during memory encoding and retrieval as well as altered functional coupling between hippocampus and the dorsolateral prefrontal cortex (DLPFC) (Grady et al, 2001;Allen et al, 2007;Dickerson and Sperling, 2008), but the relevance of these findings for heritable risk was undetermined. Previous genetic studies have led to the identification of APOE4 as an unequivocal susceptibility locus for late-onset AD (Farrer et al, 1997), with neuroimaging studies in APOE4 carriers suggesting compensatory increased recruitment of hippocampal and prefrontal regions (Bookheimer and Burggren, 2009) and evidence for disturbed white matter integrity (Honea et al, 2009;Sheline et al, 2010). Other genes, however, were less consistently implied.…”
Section: Introductionmentioning
confidence: 99%